Detrimental effects of cadmium on male infertility: A review - Nebojša Zečević; Jovana Kocić; Milan Perović; Aleksandar Stojsavljević (Ecotoxicology and Environmental Safety)
Infertility has become a serious health and socio-economic-psychological problem globally. The harmful role of trace metals in male infertility is recognized but still not sufficiently explained. Herein, a comprehensive review was conducted to elucidate the detrimental role of cadmium (Cd) on male infertility, particularly on infertility with unknown (idiopathic) causes. Peer-reviewed studies from 2000 to 2024 dealing with seminal plasma and blood Cd levels of fertile and infertile men were retrieved were interrogated with regard to strict inclusion/exclusion criteria, and then were thoroughly reviewed and analyzed. Another aim of this review was to indicate the potential effects of Cd on changes in seminogram findings. A median range of seminal plasma Cd levels from 0.2 to 1.5 µg/L can be considered safe for men’s fertility. This review strongly implies that Cd levels were notably higher in seminal plasma of infertile cases than controls. The review’s data also indicate that exposure to tobacco smoke is a major source of elevated seminal and blood Cd levels in infertile men. Newer research points to the importance of Cd in lower levels from the environment on changes in seminogram findings, primarily count, motility of spermatozoa, and their morphology. Overall, this review implies that seminal plasma Cd levels could be a good indicator of semen quality. However, new, in-depth studies are needed to confirm or reject the causal relationship of Cd with male infertility.